Model Pembangunan Daerah 3T: Studi Kasus Daerah Perbatasan Kabupaten Bengkayang - Dokman Marulitua Situmorang; Rissa Ayustia (MBIA, 2019)
Based on the introduction survey did by researcher with one of example confine area is lunar subdistrict Bengkayang Regency. That same of area still has not the public infrastructure and health is not adequate such as serem silimbau village has not electricity, clean water and infrastructure of road is bad. So that we concluded which the problem is coming from the construction some of 3T area, cause the goverment can’t see with going deep which sensibility some of 3T area which available border with the neighbour some of countries. This case seen from the border direct areas with Malaysia such us Riau Island and west kalimantan province. Two construction of areas are difference, because many factor, like sosial factor, tradition, custom tradition and geografical. The purpose of research to find out one of true model in 3T area development which direct border with the neighbour some of countries, and this model become clue for sides that redated with area goverment and central this research did based on the development survey method (development Research). Accumulition data technigue with purposevi sampling method. The result of research that the 3T area construction in kalimantan border specially jagoi babang subdistrict Bengkayang regency, in order to do the construction model based on good infrastructure and health, because the case will influence development area development based on the local learning, tradition, and area culture.